Prediction of Activity Spectra for Substances (PASS) Technology From Sambung Nyawa (Gynura procumbens (Lour) Merr) - Saristiana, Yuneka; Prasetyawan, Fendy; Savitri, Lisa (Journal of Engineering Science and Technology Management, 2025)
This study investigates the activity of various compounds as inhibitors, enhancers, agonists, antagonists, and substrates in biochemical pathways. The results indicate that the highest activity is observed in chlordecone reductase inhibition (Pa: 0.984, Pi: 0.001), followed by HIF1A expression inhibition (Pa: 0.969, Pi: 0.002) and membrane integrity agonist activity (Pa: 0.968, Pi: 0.002). Notably, several compounds exhibit significant inhibitory effects on enzymes such as peroxidase (Pa: 0.966), kinase (Pa: 0.958), and NADPH oxidase (Pa: 0.939). Additionally, CYP1A substrates and inducers demonstrate relevant metabolic interactions, indicating potential roles in drug metabolism. These findings provide insights into the pharmacological significance of these compounds, which may contribute to the development of novel therapeutic agents.